Cellular events during development of the olfactory sense organs in Drosophila melanogaster. - Ray, K.; Rodrigues, V. (Developmental Biology, 1995)
The olfactory sensilla on the antenna of adult Drosophila melanogaster develop during the first 36 hr after pupariation, from their anlagen in the cephalic disc. We have used tissue-specific beta-galactosidase expression in the enhancer trap strain A101.IF3 and the monoclonal antibody 22C10 as sensory cell markers, as well as the lineage tracer 5-bromo-2'-deoxyuridine (BrdU), to describe this process. The development of an olfactory sensillum begins with the selection of a "founder cell" (FC). These cells are distinct in that they possess large apically located nuclei revealed by beta-galactosidase expression in A101.IF3. In the following 6 hr, a few cells neighboring the FC also start expressing beta-galactosidase and together comprise a group. Cells of this group, denoted a "presensillum-cluster" (PSC), undergo at least one round of replication and give rise to all of the cells of a sensillum. A subset of the cells within each PSC and, later, all the sensory neurons are recognized by MAb22C10. The antennae of the mutant lozenge3 (lz3) lack all basiconic and some trichoid sensilla. The mutation apparently affects early steps in sensillum development and many of the FCs fail to form. Those that are present, however, proceed to form mature olfactory sensilla. Therefore, we conclude that the selection of an FC is the first step in olfactory sense organ development. Our study reveals novel aspects of sensory development in Drosophila.